2014
DOI: 10.1073/pnas.1404851111
|View full text |Cite
|
Sign up to set email alerts
|

TIM-family proteins inhibit HIV-1 release

Abstract: Significance TIM-family proteins have been recently shown to promote viral entry into host cells. Unexpectedly, we discovered that human TIM-1, along with TIM-3 and TIM-4, potently inhibits HIV-1 release. We showed that TIM-1 is incorporated into HIV-1 virions and retains HIV-1 particles on the plasma membrane via phosphatidylserine (PS), a phospholipid that is exposed on the cellular plasma membrane and the viral envelope. Expression of TIM-1 inhibits HIV-1 replication in CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 55 publications
(78 reference statements)
3
85
0
Order By: Relevance
“…It has been reported that Tim-3 is a key regulator of the exhausted antigen-specific CD4+ and CD8+ T cells that arise in both humans and mice during chronic viral infections, such as HIV, hepatitis C virus (HCV), hepatitis B virus, and lymphocytic choriomeningitis virus (LCMV) and in cancer [18][19][20]. However, the role of Tim-3 in RCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Tim-3 is a key regulator of the exhausted antigen-specific CD4+ and CD8+ T cells that arise in both humans and mice during chronic viral infections, such as HIV, hepatitis C virus (HCV), hepatitis B virus, and lymphocytic choriomeningitis virus (LCMV) and in cancer [18][19][20]. However, the role of Tim-3 in RCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNAs were prepared using a miniprep DNA isolation kit (Qiagen) and were confirmed by DNA sequence analysis. The TIM-1-expressing vector pClneo-F-TIM-1 was kindly provided by Shan-Lu Liu (45). To express TIM-3, the TIM-3 cDNA (RDC0670; R&D Systems) was digested with HindIII and SmaI and inserted into the pShuttle-CMV vector (Addgene) digested with HindIII and EcoRV.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, low TIM-3 expression by CD4 + T cells in INRs may drive excessive T h 1 immunity and persistent immune activation. Furthermore, binding of galectin-9 to TIM-3 on CD4 + T cells reduced the susceptibility of these cells to infection by HIV [27,28]. In contrast, the TIM-3 + CD4 + cell B A C Figure 5 Galectin-9 and TIM-3 expression on CD4 + T cells of healthy controls, HIV IRs and HIV INRs.…”
Section: Discussionmentioning
confidence: 99%